2015
DOI: 10.5901/mjss.2015.v6n5s2p536
|View full text |Cite
|
Sign up to set email alerts
|

Using Social Media for Research: The Role of Interactivity, Collaborative Learning, and Engagement on the Performance of Students in Malaysian Post-Secondary Institutes

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 56 publications
4
29
0
5
Order By: Relevance
“…This research supports the SMU to improve the students skills via their peer interactions [51,52]. Their satisfaction in SMU boosts their technology use, and in turn, this use enhances their skills and improves their achievement through collaboration and interaction [3,5,7,53,54]. The findings indicate that need for univeristies, colleges, and institutions to facilitate a collaboration learning environment in order to improve the students achievement this is consistent with Al-Rahmi et al, [55].…”
Section: B Discussion and Implicationssupporting
confidence: 77%
See 1 more Smart Citation
“…This research supports the SMU to improve the students skills via their peer interactions [51,52]. Their satisfaction in SMU boosts their technology use, and in turn, this use enhances their skills and improves their achievement through collaboration and interaction [3,5,7,53,54]. The findings indicate that need for univeristies, colleges, and institutions to facilitate a collaboration learning environment in order to improve the students achievement this is consistent with Al-Rahmi et al, [55].…”
Section: B Discussion and Implicationssupporting
confidence: 77%
“…The social media tools have become a trend among the members of the Net generation or digital native who were born and interacted with digital technology [4]. Recently, the various sites of social networking are becoming widespread e-learning platforms used for the purpose of knowledge-sharing and engagement in active collaborative learning [5,6,7]. The development as the assessment of the finest social connections among learners is becoming possible through these sites.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, in the case of students' language proficiency, the results found that there were significant differences of VLSs adopted by students of different language proficiency ability because students who identified as a very good were found to be employing the strategy of use and discovery more than other categories of students. The web and web-based social networking have significantly expanded in simplicity and speed for vocabulary learning, and thus social networking sites also allow for the public sharing of information, engagement, and collaborative learning (Al-Rahmi et al, 2018a;Al-Rahmi, Othman, & Yusuf, 2015c).…”
Section: Discussionmentioning
confidence: 99%
“…They were first offered by the University of Manitoba in 2008 for the purpose of connective information [8] . In addition, the focus on social engagement extended to the small face-to-face groups that point towards a better influence on MOOCs in terms of completion [9] , [10] , [11] . Recently, research on MOOCs has shifted focus from learning to highlight the different factors related to attrition [12] .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%